2023
DOI: 10.1101/2023.01.18.23284671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating associations of omega-3 fatty acids, lung function decline, and airway obstruction

Abstract: Rationale: Inflammation contributes to lung function decline and the development of chronic obstructive pulmonary disease. Omega–3 fatty acids have anti–inflammatory properties and may benefit lung health. Objectives: Investigate associations of omega–3 fatty acids with lung function decline and incident airway obstruction in adults of diverse races/ethnicities from general population cohorts. Methods: Complementary study designs: (1) longitudinal study of plasma phospholipid omega–3 fatty acids and repeated F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Similarly, Yi Wei and his team applied a two-sample Mendelian randomization method to explore the connection between gut microbiota and COPD, identifying 9 bacterial taxa nominally associated with COPD risk 9 . Furthermore, Bonnie K Patchen and colleagues found that higher levels of omega-3 fatty acids were associated with a slower decline in lung function through MR analysis 10 . However, there have been no reports on the systematic screening of potential genetic factors demonstrating a causal relationship with COPD through Mendelian Randomization.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yi Wei and his team applied a two-sample Mendelian randomization method to explore the connection between gut microbiota and COPD, identifying 9 bacterial taxa nominally associated with COPD risk 9 . Furthermore, Bonnie K Patchen and colleagues found that higher levels of omega-3 fatty acids were associated with a slower decline in lung function through MR analysis 10 . However, there have been no reports on the systematic screening of potential genetic factors demonstrating a causal relationship with COPD through Mendelian Randomization.…”
Section: Introductionmentioning
confidence: 99%
“…Lung function is crucial for overall health, as it affects daily activities and physical and mental well-being [ [1] , [2] , [3] ]. There is a push toward research that focuses on understanding factors that impact respiratory health and how they lead to changes in lung function [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%